High School Graduation Rates:Alternative Methods and Implications - Jing Miao; Walt Haney (Education Policy Analysis Archives, 2004)
The No Child Left Behind Act has brought great attention to the high school graduation rate as one of the mandatory accountability measures for public school systems. However, there is no consensus on how to calculate the high school graduation rate given the lack of longitudinal databases that track individual students. This study reviews literature on and practices in reporting high school graduation rates, compares graduation rate estimates yielded from alternative methods, and estimates discrepancies between alternative results at national, state, and state ethnic group levels. Despite the graduation rate method used, results indicate that high school graduation rates in the U.S. have been declining in recent years and that graduation rates for black and Hispanic students lag substantially behind those of white students. As to graduation rate method preferred, this study found no evidence that the conceptually more complex methods yield more accurate or valid graduation rate estimates than the simpler methods.